PEMANFAATAN WISATA PINTU GERBANG MAJAPAHIT SEBAGAI SUMBER PEMBELAJARAN IPAS BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Dewi Ellyana Nur Aini; Erik Aditia Ismaya; Lintang Kironoratri (Jurnal Muara Pendidikan, 2023)
The purpose of this study is to describe the benefits of Majapahit Kingdom Gate tourism as a source of science learning based on local wisdom for elementary school students. This study used qualitative descriptive research with ethnographic methods. This research was conducted in Muktiharjo Village, Margorejo District, Pati Regency. The primary data sources in this study are tour managers, grade IV elementary school teachers, elementary school students, and regional archives. While secondary data sources are obtained from artifacts in tourist attractions, book literature, and relevant study publications. Data collection techniques and instruments used in this study are observation, interviews, and documentation. The analysis used in this study was qualitative data analysis using the Spradley model. The results showed that Majapahit Gate Tourism has historical relics that can be used as a source of science learning for elementary school students. The use of tourism as a learning resource is very efficient for students in processing teaching and learning. Because students not only hear but can also see directly. The potential that exists in Majapahit Gate tourism is Lawang Kaputren which has historical stories in it and events or traditions that are usually carried out by residents. Both potentials can be used as a source of science learning based on local wisdom.